2013
DOI: 10.1016/j.epsl.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally resolved diatom δ18O records from the West Antarctic Peninsula over the last deglaciation

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk O record derived from a high-resolution deglacial seasonally laminated core section off the west Antarctic Peninsula (WAP) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 109 publications
(138 reference statements)
0
21
0
Order By: Relevance
“…1a) can be accounted for by glacial discharge during summer and lower contributions in spring 30 , which follows the pattern of modern observations 28 . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) can be accounted for by glacial discharge during summer and lower contributions in spring 30 , which follows the pattern of modern observations 28 . …”
Section: Methodsmentioning
confidence: 99%
“…1a). Extremely high post-glacial (13.0-12.0 ka) sedimentation rates in Palmer Deep (2.32 cm yr -1 ) and the preservation of annually laminated sediments 29 allows single taxon δ 18 O diatom samples to be concentrated from individual laminations of near-single-taxa composition and analysed to provide an insight into the seasonality of glacial discharge and melt water input to the margin at that time 30 .…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms governing these offsets in size fractions of > 75 µm are still unresolved, but may be connected with growth effects associated with larger diatoms (Schmidt at al., 2001). Whilst a recent study has identified offsets of up to 4.2 ‰ between different diatom taxa in sediments from the Antarctic coastal margin, this is linked to their habitat within the vertical water column rather than an inter-species effect related to different fractionation in individual taxa (Swann et al, 2013). A similar scenario cannot occur here in the Bering Sea as intra-seasonal water column variations in δ 18 O vary by less than 0.5 ‰ over a depth of 0-1188 m (Schmidt et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main focuses of recent marine research has been establishing the response of the Antarctic ice sheets during the rapid climatic change that accompanied the last deglaciation (see Swann et al 2013 ). This is important for understanding the susceptibility of these regions to future warming.…”
Section: Palaeoecologymentioning
confidence: 99%